(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This research aims to analyze the impact of financing the general budget deficit through external borrowing on monetary policy in Iraq for the period (2008-2024). The research relies on a comprehensive analytical methodology that combines the study of official economic data (such as the budget deficit, public debt, liquidity indicators, interest rates and inflation, the exchange rate, foreign exchange reserves, and exported currencies). The research begins by clarifying the concept of the general budget and the problem of the deficit resulting from the excess of expenditures over revenues. It also reviews the sources of financing this deficit. Through a comprehensive study of the period, the research shows that fluctuations in the budget deficit and the state’s public debt are closely linked to fluctuations in monetary policy indicators, highlighting the direct and indirect impact of fiscal policy on overall monetary and economic performance.